Molecular Chaperone Calnexin Regulates the Function of Drosophila Sodium Channel Paralytic - Xiao, Xi; Chen, Changyan; Yu, Tian-Ming; Ou, Jiayao; Rui, Menglong; Zhai, Yuanfen; He, Yijing; Xue, Lei; Ho, Margaret S. (Frontiers in Molecular Neuroscience, 2017)
Neuronal activity mediated by voltage-gated channels provides the basis for higher-order behavioral tasks that orchestrate life. Chaperone-mediated regulation, one of the major means to control protein quality and function, is an essential route for controlling channel activity. Here we present evidence that Drosophila ER chaperone Calnexin colocalizes and interacts with the alpha subunit of sodium channel Paralytic. Co-immunoprecipitation analysis indicates that Calnexin interacts with Paralytic protein variants that contain glycosylation sites Asn313, 325, 343, 1463 and 1482. Downregulation of Calnexin expression results in a decrease in Paralytic protein levels, whereas overexpression of the Calnexin C-terminal calcium-binding domain triggers an increase reversely. Genetic analysis using adult climbing, seizure-induced paralysis, and neuromuscular junction indicates that lack of Calnexin expression enhances Paralytic-mediated locomotor deficits, suppresses Paralytic-mediated ghost bouton formation, and regulates minature excitatory junction potentials (mEJP) frequency and latency time. Taken together, our findings demonstrate a need for chaperone-mediated regulation on channel activity during locomotor control, providing the molecular basis for channlopathies such as epilepsy.